Self-administered mobile phone-based high frequency diet monitoring to advance measurements of food security in Bangladesh - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The method was developed based on data from a pilot study of high-frequency smartphone data collection conducted in Rangpur District, Bangladesh. An article was published in 2021.